A national-level analysis of life expectancy associated with the COVID-19 pandemic in India - Muniyandi, Malaisamy; Singh, Pravin Kumar; Aanandh, Yamini; Karikalan, Nagarajan; Padmapriyadarsini, Chandrasekaran (Frontiers in Public Health, 2022)
IMPORTANCE: From the demographic perspective, the impact of the virus in terms of life expectancy is not clear-cut. There is a need to study the number of years lost concerning the existing average life expectancy due to COVID-19. OBJECTIVE: To estimate the impact of life expectancy due to the COVID-19 pandemic in India. DESIGN, SETTING AND PARTICIPANTS: A total reported of 399459 deaths due to COVID-19 from June 31st 2020 to June 30th 2021 in India was used for this study. We collected day wise age-specific mortality due to COVID-19 for India from the COVID-19 data repository. General mortality for India was collected from the United Nations population estimates. The abridged life table technique was used for calculating life expectancies based on all-cause mortality and COVID-19 related mortality. MortPak software was used to calculate life expectancy. The life expectancy has been compared with and without the COVID-19 pandemic. MAIN OUTCOMES AND MEASURES: Life expectancy at birth and in different age groups was estimated for with and without COVID-19 mortality. The impact of life expectancy due to COVID-19 was estimated. RESULTS: A total of 399459 deaths due to COVID-19 were distributed age-wise and their corresponding life expectancy were calculated. Mortality due to COVID-19 was higher among the age group 40 to 65 years. It suggests that COVID-19 will have an impact on 2020-2021 life expectancy by 0.12 years. CONCLUSION AND RELEVANCE: The COVID-19 pandemic in India will break the increasing trend of life expectancy and which in turn results in declining of life expectancy in the subsequent periods